Optimising energy performance of an Eco‑Home using Building Information Modelling (BIM) - Chai, Changsaar; Nur IzieAdiana, Abidin; Ali Raza, Khoso; Ling, Luenhui; Xiong, Yaoli; Gui, Hun Chuen (Springer Nature, 2022)
In a world where sustainability constantly manifests itself as the contemporaneous zeitgeist in practically every facade of our lives, it is imperative to understand the energy performances (EP) of buildings, both old and new, and explore innovative ways to optimise this cardinal aspect of building operation. In this light, we investigate the potential benefits of integrating Building Information Modelling (BIM) into EP analysis of built infrastructures. This research, in the form of a case study, has been designed to uncover equipments of high energy consumption in an Eco-Home, and subsequently to compare BIMbased simulations with the actual data measured on energy consumption. From the analysis, this study also proposes several recommendations on energy optimisation. For the purpose of EP analysis and simulation runs, Autodesk Green Building Studio (GBS) has been deployed, while 3D BIM Model of the Eco-Home was generated using Autodesk Revit. In situ energy audit revealed that the air-conditioner was the most energy-intensive equipment in the Eco-Home. Only a small variation of energy consumption was observed in actual and simulated data. Further analysis on design alternatives illustrated that the EP of the Eco-Home can be vastly improved by adopting a few measures, such as the installation of occupancy sensors to automate lighting, the integration of greywater reclamation system to reduce water consumption, and the addition of photovoltaic panels to increase renewable energy generation. However, from the same analysis, wind energy was found to be inviable due to its low level of energy potential. This paper concludes that integrating BIM and GBS into EP analysis not only improves the overall EP measurements, but also acts as an enabler for designers and building owners to compare design alternatives effectively. The advancement of BIM integration in this study offers an interesting proposition for the architectural, engineering, and construction industry especially when it comes to the enhancement of sustainability of a building.